Bargaining in standing committees with an endogenous default - Anesi, Vincent; Seidmann, Daniel J. (Oxford University Press, 2015)
Committee voting has mostly been investigated from the perspective of the standard Baron–Ferejohn model of bargaining over the division of a pie, in which bargaining ends as soon as the committee reaches an agreement. In standing committees, however, existing agreements can be amended. This article studies an extension of the Baron–Ferejohn framework to a model with an evolving default that reflects this important feature of policymaking in standing committees: In each of an infinite number of periods, the ongoing default can be amended to a new policy (which is, in turn, the default for the next period). The model provides a number of quite different predictions. (i) From a positive perspective, the key distinction turns on whether the quota is less than unanimity. In that case, patient enough players waste substantial shares of the pie each period and the size principle fails in some pure strategy Markov perfect equilibria. In contrast, the unique Markov perfect equilibrium payoffs in a unanimity committee coincide with those in the corresponding Baron–Ferejohn framework. (ii) If players have heterogeneous discount factors then a large class of subgame perfect equilibria (including all Markov perfect equilibria) are inefficient.